A Stable Model for Euro Area Money Demand: Revisiting the Role of Wealth - Andreas Beyer (European Central Bank (ECB), 2009)
In this paper we present an empirically stable money demand model for Euro area M3. We show that housing wealth is an important explanatory variable of long-run money demand that captures the trending behaviour of M3 velocity, in particular its shift in the first half of this decade. We show that the current financial crisis has no impact on the stability of our money demand model.
Keywords: C22; C32; E41; 330; cointegration; Money demand; Parameter Constancy; Vector Error Correction Model; wealth; Geldnachfrage; Kointegration; Zeitreihenanalyse; Eurozone; EU-Staaten